ASSESSMENT OF GREENHOUSE GAS (GHG) EMISSION LEVELS IN THE COAL MINING SERVICES SECTOR AT PT ANTAREJA MAHADA MAKMUR - Saputra, Deni Rahman; Triwibowo, Anton; Batubara, Haris Fadhillah (International Journal of Social Service and Research, 2024)
The mining industry has a major influence on the increase in greenhouse gas (GHG) emissions in Indonesia, especially deforestation activities and the use of fossil energy. This makes it important to study the level of greenhouse gas emissions of a mining company so that it can determine the mitigation of reducing GHG emissions released. The research aims to assess the greenhouse gas emission levels in the coal mining services sector at PT Antareja Mahada Makmur. The study provides valuable insights into the environmental impact of coal mining activities, which is crucial for informing sustainable practices and regulatory compliance. The results of this analysis show a significant increase in total A2B and stationary sources (generators) from October 2023 to September 2024 as a source of immobile emissions. The analysis shows that carbon dioxide (CO2) gas is the most dominant component in total emissions from mobile sources (A2B). The findings of this study highlight the importance of mitigation efforts, such as improving energy efficiency and the integration of renewable energy sources, in reducing emissions in the mining sector. This research could help identify gaps and propose improvements to support companies in their mitigation efforts.